How can bicycle-sharing have a sustainable future? A research based on life cycle assessment. (1st February 2021) - Mao, Guozhu; Hou, Tianyi; Liu, Xi; Zuo, Jian; Kiyawa, Abdul-Hakim Ibrahim; Shi, Pingping; Sandhu, Sukhbir
Abstract: Bicycle-sharing is experiencing explosive growth in China, and it is expected to be an environmental friendly practice, however, mass production and insufficient recycling of shared bicycles may bring great negative environmental impact. In this study, we conduct a life cycle assessment (LCA) of bicycle-sharing in China to estimate the negative environmental impacts of the stages of the whole life cycle with nine environmental impact categories. The results show that the production stage contributes to the greatest negative environmental impacts by an average rate of 81.18% among different impact categories, much higher than other stages, i.e. the use stage, daily management and transportation stage and waste treatment and recycling stage. Specifically, the use of aluminum at the production stage contributes to the most in nine environmental impacts categories (55.43% on average). And rubber is another relatively important contributor to these nine environmental impact categories (16.27% on average). In addition, the cumulative production of excessive parts is expected to bring further environmental impacts at the production stage. To promote the sustainable development of bicycle-sharing, we discuss various potential opportunities at the production and maintenance stage, materials selection for better durability and longer service life, the structure design for the ease of maintenance. Besides, at the waste treatment and recycling stage, we promote that the recycling system is necessary for generating environmental benefits considering the potential huge supply and demand of the market. The construction of a bicycle-sharing industry chain may be an effective way for the sustainable development of bicycle-sharing in the future. Highlights: Production causes the biggest negative impacts due to short life and insufficient recycling. Aluminum alloys contributes most of negative environmental impacts, followed by rubber. Excessive bicycle parts are expected to have further negative impacts. Forming an industry chain is crucial for sustainable bicycle-sharing development.